Dietary L-carnitine supplementation modifies blood parameters of mid-lactating dairy cows during standardized lipopolysaccharide-induced inflammation - Seemann, Leonie; Frahm, Jana; Kersten, Susanne; Bühler, Susanne; Meyer, Ulrich; Visscher, Christian; Huber, Korinna; Dänicke, Sven (Frontiers in Immunology, 2024)
L-carnitine, available as feed additive, is essential for the beta-oxidation of free fatty acids in the mitochondrial matrix. It provides energy to immune cells and may positively impact the functionality of leukocytes during the acute phase response, a situation of high energy demand. To test this hypothesis, German Holstein cows were assigned to a control group (CON, n = 26) and an L-carnitine supplemented group (CAR, n = 27, rumen-protected L-carnitine product: 125 g/cow/d, corresponded to total L-carnitine intake: 25 g/cow/d, supplied with concentrate) and received an intravenous bolus injection of lipopolysaccharides (LPS, 0.5 µg/kg body weight, E. coli) on day 111 postpartum as a model of standardized systemic inflammation. Blood samples were collected from day 1 ante injectionem until day 14 post injectionem (pi), with frequent sampling through an indwelling venous catheter from 0.5 h pi to 12 h pi. All parameters of the white blood cell count responded significantly to LPS, while only a few parameters were affected by L-carnitine supplementation. The mean eosinophil count, as well as the percentage of basophils were significantly higher in CAR than in CON over time, which may be due to an increased membrane stability. However, phagocytosis and production of reactive oxygen species by leukocytes remained unchanged following L-carnitine supplementation. In conclusion, although supplementation with 25 g L-carnitine per cow and day resulted in increased proportions of specific leukocyte populations, it had only minor effects on the functional parameters studied in mid-lactating dairy cows during LPS-induced inflammation, and there was no evidence of direct improvement of immune functionality.